(untitled) (Annals of Medical Research, 2021)
Aim: Heart failure (HF) is one of the most common diseases in patients over 65 years of age.It is a clinical condition which is often mortal and requires intensive care follow-up. Therefore, some tests are used to predict the diagnosis, treatment and prognosis. In this study, we aimed to compare the effect of natriuretic peptides (ProBNP) and CRP/albumin ratio on mortality and prognosis in patients who referred to the emergency department (ED) with HF. Material and Methods: The patients with ICD codes of I50 and J81 in two different hospital ED between 2018 and 2019 were analyzed retrospectively. Demographic data of the patients and the parameters planned to be studied were recorded in a Microsoft Excel 2010 file. NCSS (Number Cruncher Statistical System) 2007 software was used for the statistical analysis.Results: Our study consisted of 301 patients. A very weak positive (CRP/albumin ratio increased as the ProBNP value increased) correlation of 0.193 between ProBNP measurements and CRP/albuminratios of the participants was found to be statistically significant(r=0.193; p=0.001; p0.01).Conclusion: According to our study, no significant correlation was found between ProBNP and CRP/albumin ratio. The CRP/albumin ratio is not appropriate to be used alone to determine the definitive diagnosis and mortality in cases with acute HF. However, since there are not enough studies regarding this subject, more studies need to be done in a more extended period and with more patients.